Optimizing Adolescent Girls’ Knowledge of Leukorrhea at Ma’had Kairatun Hisan, Carawali Village, Sidenreng Rappang - Syahriani Syahriani; Hamdiyah Hamdiyah; Ariyana Ariyana; Chandra Ariyani Saputri (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Leukorrhoea, or vaginal discharge, is a reproductive health problem frequently experienced by adolescent girls and can be physiological or pathological. Lack of knowledge about reproductive health and personal hygiene is one factor that increases the risk of pathological vaginal discharge in adolescents. This community service activity aims to increase adolescent girls' knowledge about leukorrhea and its prevention efforts through health education. The activity was held at the Ma'had Khairatun Hisaan, Carawali Village, Sidenreng Rappang Regency, on May 16, 2026, with 60 adolescent girls participating. The methods used included health education using presentations and leaflets, interactive discussion and question-and-answer sessions, and evaluation of participant understanding through direct observation. The results of the activity showed an increase in participants' understanding of leukorrhea, the differences between physiological and pathological leukorrhea, the causes, signs and symptoms of abnormal vaginal discharge, the importance of personal hygiene, and steps to prevent reproductive tract infections. Participants also demonstrated high enthusiasm throughout the activity and actively asked questions related to reproductive health. This activity demonstrates that health education is an effective method for increasing adolescent girls' knowledge about reproductive health. It is hoped that similar educational activities can be carried out continuously to support the formation of clean and healthy living behaviors and improve the quality of adolescent reproductive health.